2018
DOI: 10.3390/w10010091
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Surfactant-Modified Activated Carbon for Remediation of Hexavalent Chromium from Water

Abstract: Gemini surfactants, with double hydrophilic and hydrophobic groups, offer potentially orders of magnitude greater surface activity compared to similar single unit molecules. A cationic Gemini surfactant (Propyl didodecyldimethylammonium Bromide, PDDDAB) and a conventional cationic surfactant (Dodecyltrimethylammonium Bromide, DTAB) were used to pre-treat and generate activated carbon. The removal efficiency of the surfactant-modified activated carbon through adsorption of chromium(VI) was investigated under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…In wastewater treatment, activated carbon modified by surfactant is used as an adsorbent to remove various pollutants, including organic pollutants [26,27], reactive dyes [15,21,28,29], and heavy metals [30,31]. Surfactants are classified into anionic, cationic, non-ionic, and amphoteric ions according to the type and performance of the hydrophilic group [22].…”
Section: Introductionmentioning
confidence: 99%
“…In wastewater treatment, activated carbon modified by surfactant is used as an adsorbent to remove various pollutants, including organic pollutants [26,27], reactive dyes [15,21,28,29], and heavy metals [30,31]. Surfactants are classified into anionic, cationic, non-ionic, and amphoteric ions according to the type and performance of the hydrophilic group [22].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst adsorption capacities for, for example, sepiolite may be an order of magnitude lower than synthetic systems [ 18 ] (there are many examples of studies of these materials for the treatment of metals by adsorption that show useful level of performance [ 19 , 20 ]. The focus for the future development of adsorption based systems should be on identifying adsorbent materials that are cheap and effective adsorbents in the context of the treatment scenarios (for example, at point source or to deal with diffuse pollution), to improve the effectiveness of these treatments and to ensure that no secondary pollution is produced [ 21 , 22 , 23 , 24 ]. Secondary tasks include the need for good solid/water separation and the regeneration of adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential analysis (Table 3) proved that SMAC was more stable than activated carbon. This suggested that SMAC adsorption would be persistent and hard to remove, supported by the Cr(VI) adsorption mechanism involving electrostatic interactions [18].…”
Section: Adsorption Of Cr(vi)mentioning
confidence: 99%
“…NH4 + adsorption efficiency Figures 4 and 5 indicate only a 10% difference in Cr(VI) and NH4+ cation adsorption between SMAC-T and SMAC, implying that SMAC-T's positive and negative sites were nearly identical. Adsorption of NH4 + ions and Cr(VI) ions through the process of electrostatic interaction[18], Cr(VI) ions would be adsorbed on a positive charge and NH4 + on a negative charge.…”
mentioning
confidence: 99%